2022
DOI: 10.1021/acs.joc.2c02128
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Indoles via Domino Reactions of 2-Methoxytoluene and Nitriles

Abstract: 2-Arylindoles are privileged structures widely present in biologically active molecules. New sustainable synthetic routes toward their synthesis are, therefore, in high demand. Herein, a mixed base-promoted benzylic C−H deprotonation of commercially available ortho-anisoles, addition of the resulting anion to benzonitriles, and S N Ar to displace the methoxy group provide indoles. A diverse array of 2-arylindoles is prepared with good yields (>30 examples, yields up to 99%) without added transition metal catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
(62 reference statements)
1
7
0
Order By: Relevance
“…Intensive mechanistic studies revealed that the aldehyde gets oxidized to acid, and in situ formed acid is the key intermediate in the reaction. In accordance with the abovementioned reactions involving nitriles as the starting materials, [76,77] here too transimination takes place between the nitrile nitrogen and the silyl amide nitrogen during nitrogen labelling studies which they confirmed through HRMS analysis. In addition, mechanistic studies helped them in gaining the insights in to the reaction mechanism that concludes the use of both bases LiN(SiMe 3 ) 2 /KO t Bu combination possessing interest-ing cooperativity which is essential for simultaneous oxidation of aldehydes and benzylic CÀ H bond activation followed by subsequent nitrile addition.…”
Section: Annulationsupporting
confidence: 79%
See 1 more Smart Citation
“…Intensive mechanistic studies revealed that the aldehyde gets oxidized to acid, and in situ formed acid is the key intermediate in the reaction. In accordance with the abovementioned reactions involving nitriles as the starting materials, [76,77] here too transimination takes place between the nitrile nitrogen and the silyl amide nitrogen during nitrogen labelling studies which they confirmed through HRMS analysis. In addition, mechanistic studies helped them in gaining the insights in to the reaction mechanism that concludes the use of both bases LiN(SiMe 3 ) 2 /KO t Bu combination possessing interest-ing cooperativity which is essential for simultaneous oxidation of aldehydes and benzylic CÀ H bond activation followed by subsequent nitrile addition.…”
Section: Annulationsupporting
confidence: 79%
“…As the demand for more economical and efficient method for indole synthesis remain high, later the same group in 2023 reported for the first time by modified method which involves cleavage of CÀ O bond in 2methyl anisoles for the synthesis of 2-arylindoles (Scheme 26b). [77] In this method they circumvented the usage of aryl fluorides, and instead they employed aryl ethers as the sustainable, low cost and easily available precursor. Moreover, aryl ethers are known for its inertness, and the methoxy group acts as a poor leaving group compared to fluorine derivatives.…”
Section: Annulationmentioning
confidence: 99%
“…So far, several tandem transformations were developed as follows: (1) NaN­(SiMe 3 ) 2 /CsTFA mediated one-pot aminobenzylations of aldehyde with toluene (Scheme a); (2) LiN­(SiMe 3 ) 2 /CsF-facilitated chemoselective deprotonation of 2-fluorotoluene to build indoles (Scheme b); (3) LiN­(SiMe 3 ) 2 /CsF-mediated one-pot benzylic aroylation of toluenes; and many others . These successful one-pot transformations inspired us to wonder if allylbenzene could be chemoselectively deprotonated and trapped with our in situ generated imines.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] For several years, members of our team have been interested in the preparation of indoles under transition metal free conditions. 42,43 This interest springs from our long-standing goal: to generate and functionalize carbanions derived from weakly acidic pronucleophiles under mild conditions. [44][45][46][47][48][49][50][51][52] In combining our interest in indoles with transition metalfree arylations, we focused on cyclization of 2-alkynylaniline derivatives (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…27–41 For several years, members of our team have been interested in the preparation of indoles under transition metal free conditions. 42,43 This interest springs from our long-standing goal: to generate and functionalize carbanions derived from weakly acidic pronucleophiles under mild conditions. 44–52…”
Section: Introductionmentioning
confidence: 99%